Poetics of Maithili Folk Songs: Re-defining ‘Sita’ as a Maithil Feminist (SCHOLARS: Journal of Arts & Humanities, 2026)
This research examines Maithili¹ wedding folk songs sung among the women of the Kayasth community. The main focus of the analysis is how they reinterpret the mythical “Sita” as a representation of feminist resistance and empowerment.  Maithil² women articulate their experiences expressing agency within patriarchal structures that have historically silenced them. The study uses a qualitative close-reading method to five Maithili folk songs, collected through oral transmission and family archives. The songs are analyzed through the intersection of feminist theory and empowerment theory. Drawing from Anne Donchin’s feminist ethics of structural injustice and Deborah L. Rhode’s feminist rhetorical theory, the analysis examines how the songs reimagine Sita as a figure of resilience for the women to look up to. Findings suggest that, while traces of patriarchy remain embedded within the songs, they bring out a distinct Maithil feminist consciousness, wherein Sita becomes a medium of self-definition and solidarity. These redefinitions reveal Maithili folk songs as more than cultural rituals, but as mediums to redefine what it means to be compared to ‘Sita’, and how it stands as a form of empowerment and feminist resilience.